THE EFFECT OF STRESS AND ACADEMIC RESILIENCE ON MATHEMATICAL PROBLEM-SOLVING ABILITY WITH LEARNING MOTIVATION AS AN INTERVENING VARIABLE - Afidati, Mirzanul; Setiaji, Heru Agni (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2025)
The success of students in solving mathematical problem-solving tasks is influenced by several factors. Charles and Lester explain that the factors influencing mathematical problem-solving abilities are experiential factors, affective factors, and cognitive factors. The main objective of this research is to determine the effect of academic stress on learning motivation, the effect of academic resilience on learning motivation, the effect of academic stress on mathematical problem-solving ability, the effect of academic resilience on mathematical problem-solving ability, the effect of learning motivation on mathematical problem-solving ability, the effect of academic stress on mathematical problem-solving ability through learning motivation, and the effect of academic resilience on mathematical problem-solving ability through learning motivation. The method used is a quantitative approach, with the population consisting of all eighth-grade students at SMP Negeri 2 Lasem. The sample was taken using the simple random sampling technique, and the sample determination was done using the Slovin formula with a minimum sample of 111 students. The instruments used were questionnaires and test questions that had been validated. Data analysis was conducted using the SEM PLS method with the SmartPLS version 4 application. Based on the research results, it can be concluded that there is an influence of academic stress on learning motivation with a p-value of 0.005; there is an influence of academic resilience on learning motivation with a p-value of 0.001; there is no influence of academic stress on mathematical problem-solving ability with a p-value of 0.111; there is an influence of academic resilience on mathematical problem-solving ability with a p-value of 0.000; there is an influence of learning motivation on mathematical problem-solving ability with a p-value of 0.000; there is an influence of academic stress on mathematical problem - Solving ability through learning motivation with a p-value of 0.014; there is an influence of academic resilience on mathematical problems - Solving ability through learning motivation with a p-value of 0.007.